Obsidian circulation: new distribution zones for the argentinean northwest - Caria, Mario Alejandro (2009)
The results reported in this work are part of the research thet seeking a better undestanding of ther cultural development and social relations carried out by prehispanic peoples that inhabited the western and eastern sides of the Cumbre Calchaquies-Sierras del Aconquija (Tucumán-Argentina) mountain range. There are two goals in the search for the characteristic features in the subjects: 1) Souce determiantion by XRF of nine obsidian samples from different archaological sites on both slopes of Cumbres Calchaquies (Tucumán) and 2) Analyzing obsidian distribaution ragne taking into account the findings of the first goals and comparing them with the database for other sites of the Argentinean Northwest (NOA).